TINJAUAN YURIDIS KEWENANGAN ABSOLUT PENGADILAN TATA USAHA NEGARA TERHADAP TINDAKAN PEMERINTAH (STUDI KASUS PUTUSAN NOMOR 230/G/TF/2019/PTUN.JKT) - Henri Silalahi; Evita Isretno Israhadi (Constitutum: Jurnal Ilmiah Hukum, 2023)
The State Administrative Court (PTUN) has an important role as a control or supervision institution to ensure that decisions and/or legal actions taken by the government (bestuur) remain within the legal framework. There are cases of government actions that are detrimental to citizens, such as blocking data services and/or cutting off internet access in 4 cities/regencies in Papua Province. The problem in this research is the PTUN's authority to adjudicate government actions and the conformity of Decision Number 230/G/TF/2019/PTUN-Jkt with statutory regulations. The research method used is normative juridical. The results of this research are: a. The authority of the State Administrative Court in adjudicating government actions is in accordance with the General Explanation of Law Number 30 of 2014 concerning Government Administration. Article 1 number 18 of the law confirms that the PTUN has absolute authority to judge the actions of government officials or state administrators related to the implementation or non-implementation of concrete actions in the administration of government. Then, Decision Number 230/G/TF/2019/PTUN-Jkt was deemed to be in accordance with state administrative laws and regulations. Government actions in limiting internet access are considered unlawful acts by government bodies and/or officials because they violate Article 1 number 1 of Government Regulations in Lieu of Law Number 23 of 1959/UU Number 23 Prp of 1959 concerning Emergency Situations.